(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The possibility of hollow fiber liquid phase microextraction of benzophenone with gas chromatographic determination is shown. The parameters of hollow fiber microextraction and gas chromatographic detection of benzophenone were optimized. Quantitative characteristics of microextraction were estimated: partition coefficient and enrichment factor. Micorextraction was tested using method of standard additions for aqueous solutions of benzophenone.